Immunostimulant Effect Test Of Curcuminoid Extract From Turmeric Rhizome (Curcuma Domestica Val.) In VCO On Rats Induced Cyclophosphamide Againts An Increasing Total Leukocytes And Leukocyte Differential - Damayanti, Damayanti; Yuandani, Yuandani; Satria, Denny (Publisher Cv. Inara, 2023)
Turmeric (Curcuma domestica Val.) is a traditional Indonesian plant that has many benefits. Curcuminoids are turmeric compounds known to have effects as immunomodulators and have been proven in several in vivo tests. Immunosuppressive drugs such as cyclophosphamide are widely given to improve clinical symptoms in autoimmune patients and cancer treatment which can cause susceptibility to infection.Therefore,this study aimed to determine the immunostimulating effect of curcuminoid extract from turmeric rhizome on cyclophosphamide-induced white rats. Proof of the immunostimulating effect of curcuminoid extracts was by testing the total leukocytes and leukocytesdifferential. The test results showed that curcuminoid extracts of 1 mL, 0.5 mL, and 0.25 mL increased total leukocytes and leukocyte differential (lymphocytes, neutrophils, monocytes, basophils, eosinophils) with a significant difference (p<0.05) to the Na group CMC 0.5% as a negative control. Therefore, curcuminoid extract had the potential to have an effect as an immunostimulant. The test results showed that curcuminoid extracts of 1 mL, 0.5 mL, and 0.25 mL increased total leukocytes and leukocyte differential (lymphocytes, neutrophils, monocytes, basophils, eosinophils) with a significant difference (p<0.05) to the Na group CMC 0.5% as a negative control. Therefore, curcuminoid extract had the potential to have an effect as an immunostimulant.